Conglomerate to mudstone lacustrine cycles revealed in Junggar Basin, Northwest China: Middle Permian Lucaogou and Jingjingzigou formations. (February 2022) - Olariu, Cornel; Zhang, Zhijie; Zhou, Chuanmin; Yuan, Xuanjun; Steel, Ronald; Chen, Si; Zhang, Jinyu; Cheng, Dawei
Abstract: The Junggar Basin is one of the very large, long-lived, Late Paleozoic lacustrine basins of China, developed by the closure of the early Paleozoic Junggar Ocean. The novelty of the reported research is outcrop measurements through the mid-Permian Jingzingzigou and Lucaogou formations, allowing reconstruction of interacting very coarse and very fine-grained alluvial-to-lacustrine depositional cycles within a km-thick succession of organic-rich mudstones. The deposits are interpreted as coarse grained fan deltas that extend subaqueously into Junggar lacustrine basin, depositing fine-grained muddy, sediment gravity flow deposits. The coarseness and frequency of both alluvial and subaqueous sediment gravity flows that thin and pinch out over short distances suggests that the margin of the basin was likely steep and fringed by relatively deep lake waters, but was not the main margin of sediment supply. The proposed depositional model highlights the process response to climate-driven lake-level changes around the steep lake margin. However, the coarse-grained alluvial to fan-delta cycles and the muddy lacustrine cycles occur at different thickness scales. The former (5–13 m thick) contain internal erosion surfaces and are dominated by river sheet flood and debris flow deposits and are likely incomplete due to frequent shifting, erosion and reworking of the sediments. The lacustrine cycles (few meters thick) are dominated by current-driven, very fine sandstone, siltstone and organic-rich mudstone beds with ripple lamination and graded beds, as well as dolomites during times or places where subaqueous currents were lacking. The age dating control is not detailed but we propose that depositional cycles were likely a response to Milankovitch orbital cyclicity, also suggested by previous Permian climate modeling, that cause alternating wet and dry periods and trigger tens of meters lake level changes with abrupt grainsize changes in the shallow proximal areas and more subtle changes in sediments of distal/deep lacustrine regions. The climate changes therefore cause both sediment supply changes subaerially and lake accommodation changes subaqueously, though these would also be modulated to a lesser extent in the resultant stratigraphy by autogenic responses and tectonic forcing of sediment yield. Highlights: Outcrop data describe the characteristics of Permian age lacustrine cycles in Junggar Basin of China, a first for this basin. Junggar Basin is hundreds of kms across, has 100s m thick deposits and high organic content forming hydrocarbon reservoirs. According to mapping, 10 to 15 m thick sandstone to conglomerate cycles are lateral equivalent to meters thick muddy cycles.